Orthogonal Wavelet Packets in Discrete Periodic Spaces and applications - Yang, Meixiang (Journal of Informatics and Mathematical Sciences, 2014)
This paper proposes the construction and application of orthogonal wavelet packets in discrete space $\ell^{2}(Z_{N})$. First, we give the definition and construction of orthogonal wavelet packets. Moreover, the corresponding orthogonal decomposition is proved. Then, the realization of decomposition and reconstruction algorithm is studied. Finally, a numerical example for signal processing is given, which shows that signal processing based on wavelet packets in discrete spaces can gain better effect in some cases.